PENGARUH MEDIA MONOPOLI MODIFIKASI UNTUK PENGENALAN HURUF HIJAIYAH DI TAMAN KANAK-KANAK ASSYOFA KOTA PADANG - Azmi Indah Hati; Dadan Suryana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this study is to determine how modified monopoly media affect the introduction of hijaiyah letters in Padang City's Assyofa Kindergarten. This study used a quasi-experiment as a quantitative method. A test was employed as the data collection method, and the test's goal was to determine how big of an impact this modified monopoly media had on kids' comprehension of hijaiyah letters. The homogeneity test, hypothesis test, and normality test are the data analysis techniques that are employed. After that, the data was analyzed using the SPSS 29.0 for Windows application and a difference test (t-test). The study's findings indicate that students at Assyofa Kindergarten in Padang City are introduced to hijaiyah letters at a significantly higher rate when modified monopoly media is used. with a 0.001<0.05 significance level (2-tailed). As a result, there is a big impact from using modified monopoly media to introduce hijaiyah letters.